Regenerative inverter system for DC railway system and method thereof (2007)
PURPOSE: A regenerative inverter system for a DC railway system and a control method thereof are provided to minimize the generation of harmonic injection and unnecessary reactive power by using a high performance micro processor. CONSTITUTION: A regenerative inverter system for a DC railway system includes a first voltage detector(31) for detecting a DC voltage at a direct current supply line, a power converter(34) for converting the detected voltage into a 3-phase AC voltage, a low pass filter(35) for filtering a output voltage of the power converter, a second voltage detector(36) for detecting an output voltage from the low pass filter, a first current detector(37), a third voltage detector(38), and a controller(32). The first current detector detects an output current from the low pass filter. The third voltage detector detects an AC voltage outputted from an inverter transformer. The controller includes a power controller(32a), an instantaneous current controller(32b), and a space vector pulse-width modulation waveform generator(32c).